Pengaruh Akupressur terhadap Intensitas Mual Muntah pada Ibu Hamil Trimester I - Ana Mariza; Eka Rohmayanti; Ike Ate Yuviska; Vida Wira Utami (Malahayati Nursing Journal, 2022)
ABSTRACT   Nausea (nausea) and vomiting (emesis gravidarum) are normal in pregnant women, but if nausea and vomiting occur 10 times a day, it can disrupt the balance of nutrition, electrolytes, and can affect the general condition so that if vomiting increases to hyperemesis it can result in impaired fetal growth. Efforts to reduce the frequency of vomiting can be given several actions such as drugs, besides drugs, nausea in early pregnancy can be reduced by using complementary therapies such as acupressure. Acupressure is a massage method based on the science of acupuncture or it can also be called acupuncture without needles. The purpose of the study was to know the effect of acupressure with nausea and vomiting in pregnant women TM I at PMB Gusnila, Pringsewu Regency in 2021. This type of quantitative research is a quasi-experimental approach with a one group pre-post test design approach. The population of this study were all 32 pregnant women who were about to give birth, with a sample of 30 respondents. The object of this research is pregnant women with TM I who experience nausea and vomiting. The research was carried out at PMB Gusnila Pringsewu in June - July 2021. Data collection used questionnaires and observations. Data analysis was univariate and bivariate (Wilcoxon test). The results showed that the average nausea and vomiting before being given acupressure therapy was 8.9, while the average nausea and vomiting after being given acupressure therapy was 6.5. There is an effect of acupressure on nausea and vomiting in TM I pregnant women at PMB Gusnila, Pringsewu Regency in 2021 with a p-value = 0.000. acupressure therapy can be applied as a non-pharmacological therapy to reduce the frequency of nausea and vomiting in pregnancy. Keywords: Nausea Vomiting, Acupressure Therapy, and Pregnant Women  ABSTRAK Mual (nausea) dan muntah (emesis gravidarum) suatu yang normalpada ibu hamil namun jika mual muntah terjadi 10 kali dalam sehari, dapat mengganggu keseimbangan gizi, cairan elektrolit, dan dapat memengaruhi keadaan umum sehingga jikamuntah bertambah menjadi hiperemesis dapat mengakibatkan pertumbuhan janin terganggu. Upaya untuk mengurangi frekuensi muntah dapat diberikan beberapa tindakan seperti obat, selain obat, rasa mual pada awal kehamilan dapat dikurangi dengan menggunakan terapi komplementer seperti akupresure. Akupresur adalah cara pijat berdasarkan ilmu akupuntur atau bisa juga disebut akupuntur tanpa jarum. Tujuan penelitian diketahui pengaruh akupresur dengan mual muntah pada Ibu Hamil TM I di PMB Gusnila Kabupaten Pringsewu Tahun 2021. Jenis penelitian kuantitatif pendekatan quasi esksperiment dengan pendekatan one group pre – post test design. Populasi penelitian ini adalah seluruh ibu yang akan bersalin berjumlah 32 ibu hamil, dengan sampel sebanyak 30 responden. Objek penelitian ini adalah ibu hamil TM I yang mengalami mual muntah. Penelitian telah dilaksanakan di PMB Gusnila Pringsewu pada bulan Juni - Juli 2021. Pengumpulan data menggunakan kuesioner dan observasi. Analisi data secara univariat dan bivariat (uji wilcoxon). Hasil penelitian diketahui rata-rata mual muntah sebelum diberikan terapi akupresur adalah 8,9, sedangkan rata-rata mual muntah setelah diberikan terapi akupresur adalah 6,5. Ada pengaruh akupresur terhadap mual muntah pada ibu hamil TM I di PMB Gusnila Kabupaten Pringsewu Tahun 2021 dengan nilai p-value = 0,000. terapi akupresur dapat diterapkan sebagai terapi non farmakologi untuk mengurangi frekuensi mual muntah pada kehamilan. Kata Kunci: Mual Muntah, Terapi Akupresur, dan Ibu Hamil